PENGARUH PENABURAN ZEOLIT PADA LANTAI LITTER TERHADAPPERSENTASE KARKAS DAN KOMPQN(EN NON KARKAS AYAM PEDAGING PADA KEPADATAN KANDANG YANG BERBEDA - Dede Kardaya; Niken Ulupi (State Islamic University of Sultan Syarif Kasim Riau, 2005)
Spreading zeolites on litter floor of broiler house at rate of 5.0 kg/m2 increased broiler carcass percentages up to 5.41 percents. Effect of zeolites-spread litters on broiler carcass and non-carcaSs components under different floor spaces had been performed in five weeks. As many as 324 chicks of a day-old Hubbard strain were fed with rations contained 3,000 -3,100 Kcal/I<g ME and 21 %crude protein during starter period and fed with the ration contained 20% crude protein duringfinisher period. The chicks were allocated to three different floor spaces (10, 12, and 14 heads/m2) and three different zeolites-spread litters (0.0, 2.5, and 5.0 kg zeolites/m2) under completely randomized design with factor 3 x 3 and 3 replications. Parameters concerned of present research including percentages of both carcasses and non-carcass components were analyzed with analysis of variance (ANOV A) and least .significant different.Results of the preseqt research showed that there was no interaction effect between floor spaces and zeolites-spread litters on all parameters concerned. Floor spaces affected the percentages of gizzard, kidney, and spleen significantly (p<O.05) but neither carcass nor abdominal fat percentage was af.fectedby the floor space. The zeolites-spread litters only affected significantly (P<O.05) on carcass percentage. Spreading zeolites at rates of5.0 kg/m2 on litter floor resulted in the highest carcass percentage (p<O.05) while rates of 25 kg/m2 resulted the same carcass pen:entage as the rates of 0.0 kg/m2. It was concluded that spreading zeolites at rates of 5.0 kg/m2 on litter floor under different floor spaces increased can:ass percentages up to 5.41 percents.